Sistemática do jupati Metachirus Burmeister, 1854 (Mammalia: Didelphimorphia) - Vieira, Carlos Leonardo Gomes Cezar (2006)
I analyzed a sample of 248 specimens from four mammal collections in Brazil aiming at systematic studies of the genus Metachirus. Since systematic studies based on morphological data usually rely on the definition of age classes, I used traditional morphometrics to determine which group of dental age classes shows the lowest level of statistical differences through ontogenetic development. I also evaluated secondary sexual dimorphism in three populations of this taxon across the Brazilian Amazon. The results showed that the best grouping includes adults of age classes 6 and 7, which have the lowest levels of statistical differences among measured variables. One of the three populations evaluated presented no statistical differences regarding sexual dimorphism and, in the other two populations, only a few cranial measurements showed dimorphism. I conclude that sexual dimorphism is present in Amazonian populations of Metachirus, but to a lesser degree than in other didelphid marsupials